2011
DOI: 10.14236/ewic/hci2011.52
|View full text |Cite
|
Sign up to set email alerts
|

A Design Framework for Mediated Personal Relationship Devices

Abstract: Substantial numbers of people carry out intimate relationships at a distance. These people have to utilise a variety of communication technologies in order to maintain their relationship. Although a number of communication technologies have been developed to help maintain an emotional connection between remote couples, there has been no comprehensive consideration of the design space that these technologies are developed within. We present here a proposed design framework for intimate communication devices. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(5 reference statements)
1
9
0
Order By: Relevance
“…Our findings lend support to existing design frameworks which have identified the potential for effort to be encouraged by mediating technologies [e.g. 20,27] but which were lacking first-hand evidence of its potential.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings lend support to existing design frameworks which have identified the potential for effort to be encouraged by mediating technologies [e.g. 20,27] but which were lacking first-hand evidence of its potential.…”
Section: Resultssupporting
confidence: 79%
“…We consciously decided to develop a distinct communication tool rather than adapting a pre-existing technology (for example, a plug-in for Facebook Messenger). Previous work has indicated that, in some circumstances, close personal relationships can benefit from using technologies that only people in that relationship can use [20]. Ten participants across seven pairs discussed the value of this one-to-one connection.…”
Section: Channel Exclusivitymentioning
confidence: 99%
“…This function of effort in close relationships has been acknowledged in the HCI literature on communication technologies [15]. Qualitative investigations have identified that the investment of time and effort into messaging is highly meaningful to people and is seen as reflecting a person's commitment to the exchange [27,28,37].…”
Section: The Value Of Effort In Relational Technologiesmentioning
confidence: 96%
“…In addition to mediating lightweight exchanges, HCI research has recently drawn attention to the potential for communication systems to demand effort from the persons involved [e.g. 15,28,37,39]. This is based on the fact that people recognise the value of effort when communicating with close relational partners [24] and because people value systems which make their effort clear to message recipients [28].…”
Section: Introductionmentioning
confidence: 99%
“…Pace et al [12] studied virtual world as a source of intimacy and found permeability across virtual and real worlds, mundane as origin of intimacy, reciprocity and exchange, and temporality in shaping intimate experience. Gooch & Watts [13] proposed a framework to formalize the design space for intimate communication devices. They have highlighted the 6 factor of Personalization, Sensory Medium, Effort, Openness of the System, Metaphor of Use, and Fleeting vs Realized Output.…”
Section: Human Factor Elicitation For Design Of Intimate Mediummentioning
confidence: 99%